Cryptobiota associated to dead Acropora palmata (Scleractinia: Acroporidae) coral, Isla Grande, Colombian Caribbean - Silvia K. Moreno-Forero; Gabriel R. Navas S.; O.David Solano (Revista de Biología Tropical, 1998)
Cryptobiota of dead fragments of five branches in live position and five fallen pieces of the coral Acropora palmata each one of approximate 1dm3, covered by filamentous algae were extracted from the north reef crest of Isla Grande (Colombian Caribbean), in April 1991. There were three groups of organisms according to size and position (on and within the coral): 1) mobile epibenthos, mainly microcrustaceans that live among the filamentous algae 2) boring microcryptobiota, located in the layer between the epilithic organisms and the coral skeleton itself and, 3) perforating macrocryptobionts that bore and penetrate the coral skeleton. Polychaetes, sipuncu-lids, mollusks and crustaceans were most abundant in the last group. There were no differences in macrocryptobiont composition between standing dead branches and fallen fragments. There was a large variation in total biomass and type and density of macro-cryptobionts, possibly associated to stochastic factors such as placement and thickness of branches and small scale variations in recruitment La criptobiota de diez fragmentos coralinos muertos de Acropora palmata, de 10 dm3 cada uno, cubiertos de algas filamentosas, se colectó en abril de 1991en la cresta arrecifal de Isla Grande (Caribe colombiano). Se halló tres grupos: 1) móviles epibentónicos asociados a las algas filamentosas y conformados principalmente por microcrustáceos; 2) microcriptobiontes perforantes, ubicados en la capa intermedia entre los organismos epilíticos y el esqueleto del coral y 3) macrocriptobiontes que perforan todo el cuerpo del esqueleto coralino (principalmente poliquetos, sipuncúlidos, moluscos y crustáceos). No se encontraron diferencias en la composición de los macrocriptobiontes que habitan los corales en posición de vida y los fragmentos caidos sobre el fondo. Se presentó una amplia variación en biomasa total, tipo y densidad de macrocriptobiontes, posiblemente asociada a factores estocásticos tales como la ubicación y grosor de las ramas, y variaciones del reclutamiento a pequeña escala.